Inquiry and Inquisition: Academic Freedom in Medieval Universities - Courtenay, William J. 1935- (1989)
The year 1988 marks not only the centennial of the American Society of Church History, it is also the anniversary of two important works dealing with the theme of religious toleration and freedom of ideas. One is the fiftieth anniversary of G. G. Coulton's Inquisition and Liberty. The other is Henry Charles Lea's History of the Inquisition of the Middle Ages, published in three volumes early in 1888. Coulton's work became a model for many that followed: a highly readable, consciously engaging narrative outlining the main features of one of the darker chapters of medieval church history. It covered the development of religious nonconformity, the church's response, especially through the creation and operation of the Inquistion, and the principal victims of the Inquisition: the Albigensians, Waldensians, Spiritual Franciscans, and those accused of witchcraft. Lea's earlier treatment covered those themes in a far more extensive way, and he also included, unlike Coulton, a final chapter on the problem of religious orthodoxy in the schools as viewed from the standpoint of the Inquisition. Lea, in fact, is one of the few authors writing on heresy and inquisition who attempted to place the cases of questioned orthodoxy and freedom of thought in medieval schools and universities in this larger context. Although he did not pursue the topic in any depth, Lea was aware that the character of theological study and the proper training of an educated priesthood were linked to the issue of religious orthodoxy in the schools and the threat of heresy among those charged with the preservation and dissemination of truth.